LOW BIRTH WEIGHT AND IMMUNIZATIONS STATUS: RISK FACTORS OF ACUTE RESPIRATORY INFECTION IN CHILDREN 2-5 YEARS - Qonita Rahmadiena; Erika Diana Risanti; Listiana Masyita Dewi; Shinta Riana Setiawati (Universitas Ahmad Dahlan, 2021)
Background: Acute Respiratory Infection (ARI) is one of the most important causes of morbidity and mortality in children under five years old (toddlers) worldwide, especially in developing countries. ARI is an acute upper or lower respiratory tract disease that occurs acutely, usually transmitted with mild to lethal symptoms. Various risk factors cause a high incidence of ARI cases in infants, including low birth weight (LBW) and incomplete immunization. Children aged 2-5 years are expected to have received basic immunizations and complete tests according to age to have a stronger immunity to ARI than children aged less than two years. Objective: To determine the relationship of LBW and immunization history with ARI events in children aged 2-5 years.Methods: This is an analytic observational study with a cross-sectional design using 31 samples of ARI and non-ARI pediatric patients treated at the PKU Muhammadiyah Hospital Surakarta. Samples were determined using a purposive technique - meaning that samples were taken according to specific criteria. The population was pediatric patients aged 2-5 years diagnosed with ARI: common cold, nasopharyngitis, tonsillitis, laryngitis, bronchitis, bronchiolitis, pneumonia, and SARS. This study's study populations are pediatric patients aged 2-5 years who were outpatient at PKU Muhammadiyah Hospital Surakarta in December 2019. Therefore, the number of samples is calculated using the Sample Formula for Study Groups with Different Sample Sizes, and data was taken employing a patient's parent interview.Results: There were 31 patients with details of 17 ARI and 14 non-ARI. Fisher's test showed there was no relationship between LBW and ARI (p-value = 0.597, p> 0.05 and Prevalence Ratio = 1.286). And there was no significant relationship between the history of immunization with ARI (p-value = 0.287, p> 0.05 and Prevalence Ratio = 2.5).Conclusions: There is no significant relationship between LBW and immunization history with ARI in children aged 2-5 years.